Marketing for Relevance, Visibility, and Sustainability: Exploring the Views of Greek Library Professionals - Vraimaki, Eftichia; Briana, Maria; Koloniari, Maria; Takatoglou, Alkmini (Journal of Integrated Information Management, 2023)
Purpose - Libraries worldwide are struggling with issues of relevance and necessity. Despite substantial transformations, especially due to the COVID-19 pandemic, their services often fail to meet users’ needs or remain largely unknown to the public. This study aims to examine the attitudes, activities, challenges, and competencies related to marketing among Greek library professionals to enhance the relevance, visibility, and sustainability of their libraries. Design/methodology/approach – This research involves surveying Greek library professionals to gather data on their perceptions and practices regarding marketing. Using a quantitative research design, the study evaluates their recognition of marketing’s importance, self-assessed marketing skills, and the extent of marketing activities and planning in their libraries. Findings - The findings reveal that while library professionals acknowledge the importance of marketing and believe they possess the necessary skills to promote their collections and services, there is a significant lack of prioritization and investment in marketing from library management. Additionally, marketing efforts are often unplanned and sporadic. The study discusses the practical implications of these findings for leadership within libraries and the education provided in Library and Information Science (LIS) programs. Originality/value - This study provides valuable insights into the marketing practices and challenges faced by Greek library professionals. It underscores the need for better planning and investment in marketing initiatives and highlights the importance of integrating marketing education into LIS programs to prepare future librarians for these crucial tasks.